AESTHETIC OPTIMIZATION COMBINING TEETH WHITENING, DIRECT VENEERS, AND DIASTEMA CLOSURE WITH COMPOSITE RESIN - CASE REPORT (CIPEEX, 2025)
Aesthetics is a factor that involves people's daily lives, relating social, cultural, and psychological factors, and teeth are very important in this context. The presence of teeth with any kind of disharmony, especially in the anterior segment of the mouth, is one of the main aesthetic problems that negatively affect people. Dentistry allows changes to be made to individuals' smiles through whitening techniques and composite resin restorations. Objective: To improve the patient's relationship with their self-image through teeth whitening and direct aesthetic restorative procedures. Case report: Patient KFM, male, sought treatment at the UniEVANGÉLICA Dental Teaching Clinic with the main complaint that he would like to replace a restoration on his front tooth and change its color, as it was very yellow and there were diastemas between his upper incisors. The clinical examination showed tooth 21 with a very evident brownish color, the other teeth yellowish, and the presence of diastemas between the upper incisors. After studying the case, a diagnostic waxing was performed to resize the teeth. The proposed treatment plan was teeth whitening, followed by restorative procedures, within the clinical protocol, which included: closing the diastemas and performing direct veneering with composite resin on tooth 21. Conclusions: Teeth whitening, a minimally invasive procedure, met expectations, and direct-use composite resins promoted immediate and satisfactory aesthetic results, achieving the desired aesthetic success and patient satisfaction. Keywords: Composite Resins; Dental Aesthetics; Smile; Self-Image.
Keywords: Composite Resins; Dental Aesthetics; Smile; Self-Image